2021
DOI: 10.3390/nu13093111
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Nutrition and Mental Health: The Role of DNA Methylation

Abstract: Does the quality of our diet during early life impact our long-term mental health? Accumulating evidence suggests that nutrition interacts with our genes and that there is a strong association between the quality of diet and mental health throughout life. Environmental influences such as maternal diet during pregnancy or offspring diet have been shown to cause epigenetic changes during critical periods of development, such as chemical modifications of DNA or histones by methylation for the regulation of gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 119 publications
1
35
0
Order By: Relevance
“…Maternal mental health: There is a relationship between maternal nutrition and well-being during pregnancy, 31 and a retrospective cohort analysis showed that folate was positively and significantly associated with well-being in a pregnant population. 32 Another small cohort study found that postpartum depression was lower with folic acid supplementation when taken for more than 6 months of the pregnancy when compared with those who took folic acid for less than 6 months.…”
Section: Benefits and Risks For Pregnant Womenmentioning
confidence: 99%
“…Maternal mental health: There is a relationship between maternal nutrition and well-being during pregnancy, 31 and a retrospective cohort analysis showed that folate was positively and significantly associated with well-being in a pregnant population. 32 Another small cohort study found that postpartum depression was lower with folic acid supplementation when taken for more than 6 months of the pregnancy when compared with those who took folic acid for less than 6 months.…”
Section: Benefits and Risks For Pregnant Womenmentioning
confidence: 99%
“…Early life nutrition can modulate the epigenome through different mechanisms: the change in the structure of chromatin through histone modifications and the supply of methyl donors (i.e., methionine, choline, folate), the activity of DNA methyltransferases, and of specific transcription factors. In this way, altered maternal nutrition may induce epigenetic changes in the global expression pattern of the fetus, which will trigger biological and psychological alterations in offspring's lifelong outcomes [136][137][138][139].…”
Section: Nutrition and Environmentmentioning
confidence: 99%
“…[44] Other studies demonstrated the role of dietary micronutrients during early life in altering gene expression and influencing health or disease later in life. [45,46] In adults, large-scale analysis of DNA methylation in leukocytes, for example, identified differentially methylated CpG sites associated with folate or vitamin B 12 intake. [47] A study of habitual diet quality, including the Mediterranean diet score and the Alternative Healthy Eating Index, reported an association with differential leukocyte DNA methylation levels of 30 CpG sites, most of which were also associated with adverse health outcomes.…”
Section: Evidence For Epigenetic Effectsmentioning
confidence: 99%
“…[ 44 ] Other studies demonstrated the role of dietary micronutrients during early life in altering gene expression and influencing health or disease later in life. [ 45,46 ]…”
Section: Introductionmentioning
confidence: 99%